2020
DOI: 10.1155/2020/5956732
|View full text |Cite|
|
Sign up to set email alerts
|

Nutritional Status and Educational Performance of School-Aged Children in Lalibela Town Primary Schools, Northern Ethiopia

Abstract: Background. Every student has the potential to do well in school. Failing to provide good nutrition puts them at risk for missing out on meeting that potential and leads to long-term irreversible damage to cognitive development. However, taking action today to provide healthier choices in schools can help set students up for a successful future full of possibilities. So, this study is aimed at assessing the effect of nutritional status on academic performance of school-aged children. Methods. A school-based cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
0
8
1
3
Order By: Relevance
“…It is comparable with the results of the study conducted in Haik Town, Northeastern Ethiopia [ 26 ], Fogera and Libo Kemkem Districts, Northwestern Ethiopia [ 27 ], and Arba Minch, Southern Ethiopia [ 28 ]. However, it was higher than the study results conducted in Lalibela Town, Northern Ethiopia where 29.5% of subjects were stunted [ 29 ], Northwestern Ethiopia where 37.9% were stunted [ 30 ], in Dale Woreda, Southern Ethiopia where 25.6% were stunted [ 7 ], and Addis Ababa Ethiopia where only 19.6% were stunted [ 24 ]. Similarly, it was higher than the study conducted in Urban slums in India [ 31 ], South India [ 32 ], and Nairobi Peri-Urban Slum of Kenya [ 33 ] where 18.5%, 19.3%, and 30.2% of children were stunted, respectively.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…It is comparable with the results of the study conducted in Haik Town, Northeastern Ethiopia [ 26 ], Fogera and Libo Kemkem Districts, Northwestern Ethiopia [ 27 ], and Arba Minch, Southern Ethiopia [ 28 ]. However, it was higher than the study results conducted in Lalibela Town, Northern Ethiopia where 29.5% of subjects were stunted [ 29 ], Northwestern Ethiopia where 37.9% were stunted [ 30 ], in Dale Woreda, Southern Ethiopia where 25.6% were stunted [ 7 ], and Addis Ababa Ethiopia where only 19.6% were stunted [ 24 ]. Similarly, it was higher than the study conducted in Urban slums in India [ 31 ], South India [ 32 ], and Nairobi Peri-Urban Slum of Kenya [ 33 ] where 18.5%, 19.3%, and 30.2% of children were stunted, respectively.…”
Section: Discussionmentioning
confidence: 78%
“…The prevalence of wasting was 35.44% (16.48% severely wasted). It was the highest magnitude than in other studies conducted in Gondar town, North West Ethiopia 9% [ 16 ], Arba Minch, southern Ethiopia 8% [ 28 ], Fogera and Libo Kemkem Districts, 21.6% [ 27 ], in Dale Woreda, Southern Ethiopia (14%) [ 7 ] and Lalibela Town, Northern Ethiopia (29.5%) [ 29 ]. The differences in the studies' study period, study design, study area, and dietary intervention activities could be to blame for the inconsistencies.…”
Section: Discussionmentioning
confidence: 82%
“…Schooling levels can be seen as the re ection of age at school enrollment and grade repetition, and are thus dependent on academic performance. Several studies have highlighted that stunted growth and height-for-age are associated, respectively, negatively and positively with test results in mathematics, reading, communication and motor development [6,21,[45][46][47][48][49]. Results showed that impaired growth and development in infancy negatively affects later academic performance and therefore academic trajectory, which leads, overall to low school levels.…”
Section: Discussionmentioning
confidence: 99%
“…Indonesia menempati urutan ke 107 pada Human Development Indicators pada tahun 2020 dengan nilai indeks dari 189 Negara dan Wilayah (United Nations Development Programs, 2020). Berdasarkan penelitian Ayalew di Afrika bagian utara, 14,7% dari peserta penelitian yang mengalami malnutrisi memiliki kemampuan akademik rendah prestasi di semester tersebut (Ayalew et al, 2020) .…”
Section: Pendahuluanunclassified